Quality management system for university teacher training processes based on ISO 9001: 2015 - Delgado Bardales, José Manuel (2020)
The various agencies that monitor and control the level of quality of process management to provide university educational service have increased their demand, forcing institutions to implement continuous improvement, in that sense a model of Management System has been designed of Quality based on ISO 9001: 2015 that favors the processes of training and continuing education of university teachers, the type of research is descriptive, the population was composed of 311 ordinary teachers and 33 responsible for the management of the study process, obtaining a sample of 75 and 33 respectively, two questionnaires were used as instruments to collect information and obtain with the processing of the data the confirmation of the problem described in this investigation, in this sense the results were; that in the processes of training and continuing education of the National University of San Martin is deficient in 44.0% and regular in 34.7%, regarding the progress of implementation of the Quality Management System is deficient with 57.3% and regular in a 32.0% concluding that the application of a Quality Management System based on ISO 9001: 2015 is urgently needed to help improve in particular the process of training and continuous training.